Pengaruh Sikap Kerja, Kualitas Kerja, Keterampilan, dan Efisiensi terhadap Produktivitas Kerja Karyawan Bagian Produksi PT Mister Burger Pelita Harapan Indonesia The Influence of Work Attitudes, Quality of Wo - Lestari, Maria Mariati; Triana, Dewi; Widiyanti, Anik (EBBANK, 2024)
Employee work productivity determines the success of a business. This study aims to determine the effect of work attitude, quality of work, skills, and efficiency on work productivity of employees of the Production Department of PT Mister Burger Pelita Harapan Indonesia. Data collection in this study was carried out through a survey approach with quantitative descriptive research. The sample in this study used a saturated sample with a total of 37 employees working in the production department at PT Mister Burger Pelita Harapan Indonesia. The data analysis tools used in this study were multiple regression, t-test, and F-test. The results of the study show that partially the quality of work and skills have a significant effect on employee work productivity. However, work attitude and efficiency have an effect but not significant on employee work productivity. The results of simultaneous or simultaneous testing show that work attitude, work quality, skills and efficiency have a significant effect on employee work productivity.